The influencing factors of deliberative capacity and their configuration paths from the perspective of deliberative system: a fuzzy set qualitative comparative analysis of 30 cases - Han Wang; Hui Xie; Lulu Zhu; Siqi Liang (Frontiers in Political Science)
An effective measure to enhance the overall deliberative capacity of society is to promote large-scale deliberation by constructing and improving a deliberative system. Based on Dryzek's theory of deliberative system and the practical experience of Chinese grassroots deliberation, this paper conducts a configuration analysis of the influencing factors and their configuration paths of 30 cases' deliberative capacity. The results show that: all components of the deliberative system have important effects on the deliberative capacity, but no single component constitutes the necessary condition for high deliberative capacity; there are three configuration paths that give rise to high deliberative capacity, which can be divided into two types: government-single-driven type and government-society-dual-driven type. Deliberative systems with different maturity can obtain high deliberative capacity as long as they adopt the correct configuration paths; The influence of the components of a deliberative system on deliberative capacity will change with the variations of maturity of the deliberative system.